Analisis Koreksi Fiskal Atas Laporan Keuangan Perusahaan Pada Pt Trijaya Sarana Mandiri Di Bandar Lampung - Aditya Kristianto; Aminah Aminah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Fiscal correction is a correction of financial records to comply with tax regulations. This study aims to determine whether the financial statements of PT Trijaya Sarana Mandiri has complied with tax regulations in calculating corporate income tax, the type of fiscal correction made, and the impact of the fiscal correction on the amount of corporate income tax owed by PT Trijaya Sarana Mandiri The data analysis method used in this study is descriptive analysis, in which the researcher analyzes the commercial financial statements of PT Trijaya Sarana Mandiri, make fiscal corrections, and determine the amount of income tax payable in accordance with tax provisions. The results of the study show that the calculation of corporate income tax for PT Trijaya Sarana Mandiri is not in compliance with tax provisions, fiscal corrections are made in the form of positive corrections, and the impact on tax payable increases tax payable. The impact of this fiscal correction can increase Taxable Income and Tax Payable, and can reduce the net profit of PT Trijaya Sarana Mandiri.